Seagrass Condition at Some Small Islands in The Taka Bonerate National Marine Park, South Sulawesi Indonesia - Indarto Happy Supriyadi; Hendrik Alexander William Cappenberg; Sam Wouthuyzen; Muhammad Hafizt; Susi Rahmawati; La Ode Alifatri; Suyarso Suyarso (Jurnal Segara, 2021)
The assessment of seagrass bed condition in Indonesia still refers to the Decree of the State Minister for the Environment (KMNLH) no. 200 of 2004, which considers only one variable, namely the percentage of seagrass cover. To assess the seagrass beds condition to be more in-depth and meaningful, it is necessary to consider the addition of several variables, such as the biotic variables (seagrass species diversity including macroalgae and macro-benthos components) as well as the abiotic variables (reef flat areas and the substrate components). The purpose of this study is to determine the seagrass beds condition in several small islands in the Taka Bonerate National Marine Park by considering the additional analysis using both biotic and abiotic variables as mentioned above. The methodology used in this study is a combination of the use of the standard seagrass transect method, interpretation of satellite imagery related to the seagrass bottom habitat area, and its components on the reef flat of a particular island, as well as weighting and scoring based on those considered additional variables. By applying the criteria in the method, the seagrass bed conditions were then classified into three categories, namely seagrass in good, moderate, and unfavorable conditions, respectively. The results of the total score assessment on several small islands in Taka Bonerate Islands show that the seagrass bed in Latondu Besar Island is in good conditions with the highest score of (316) compared to Tarupa Besar, Jinato, Rajuni Kecil, and Tinabo Besar Islands with an average score of (173). The results of this study indicate that the assessment of seagrass conditions is more meaningful in terms of seagrass ecology than based on seagrass cover alone. However, this study requires a lot of validation for its application in assessing the condition of seagrass beds in other islands in Indonesia.